Multifarious roles of lipid droplets in autophagy – Target, product, and what else?. (December 2020) - Ogasawara, Yuta; Tsuji, Takuma; Fujimoto, Toyoshi
Abstract: Lipid droplets (LDs) are not an inert storage of excessive lipids, but play various roles in cellular lipid metabolism. Autophagy involves several mechanisms for the degradation of cellular components, and is related to many aspects of lipid metabolism. LD and autophagic membranes often distribute in proximity, but their relationship is complex. LDs can be degraded by autophagy, but LDs are also generated as a result of autophagy or support the execution of autophagy. Moreover, several proteins crucial for autophagy were shown to affect different aspects of LD formation. This article aims to categorize this multifaceted and seemingly entangled LD–autophagy relationship and to discuss unresolved issues.